Literature Study: Analysis of STEAM-Based Physics Learning Practices to Train Students' Creative Thinking Skills - Rahman, Ridwan Akbar Nur; Sucahyo, Imam; Anggaryani, Mita; Citra, Nina Fajriyah (Studies in Physics Teaching and Learning, 2025)
In conjunction with the rapid advancement of science and technology, current education system necessitates transformative changes to align with the evolving demands of the 21st century. As current issues require multidisciplinary solutions, STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach offers an opportunity to expand students’ analytical perspectives while simultaneously developing the skills needed to thrive in the 21st century, including creative thinking that appears as one of the valuable skills that enables students to identify problems and formulate effective solutions. Thus, this study aims to analyze previous studies regarding the practices of STEAM-based physics learning among high school students in incorporating creative thinking skills. These papers will be used to assess the extent of creative thinking development in STEAM-based physics education. The research method was carried out by collecting data from relevant literature pertinent to the research objectives. Based on literature review, the findings indicate that the STEM-based 5E learning model effectively equips students with the critical thinking and problem-solving skills essential for the 21st century. The application of the STEAM approach, coupled with the assistance of spectra-plus on sound wave material, has significantly enhanced the 21st-century skills of students. This approach has fostered collaborative and effective communication among students, enabling them to identify existing problems through comparative observations. By analyzing the results of their observations, students are empowered to devise solutions to existing challenges.